2016
DOI: 10.1007/s10870-016-0649-8
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Crystal Structure, and Spectroscopic Properties of Cu(II) Complex with 14-Membered Hexaazamacrocyclic Ligands

Abstract: CuL(ClO 4 ) 2 ] complex of 14-membered hexaazamacrocyclic ligand (L = 6,13-dimethyl-3,10-dioctyl-1,3,5,8,10,12-hexaazacyclotetradecane) was synthesized by template condensation reaction of 1,2-diaminopropane, octylamine, and formaldehyde in ethanol. The product was characterized by elemental analysis, Fourier-transformed infrared spectroscopy (FT-IR), ultraviolet-visible spectroscopy (UV-vis), diffused reflectance spectroscopy (DRS), liquid chromatography-mass spectrometry (LC-MS), and X-ray crystallographic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…The splitting of ν(Cl-O) band clearly indicated the presence of coordinated perchlorate. 21 In complex 2, the FT-IR spectrum ( Figure S2, in Supplementary Information) showed strong band at 3247 cm −1 which was assigned to secondary amine group. The vibrations from cyanide ligand may vary depending on the bonding mode, 22 24 the two absorption bands observed at 2117 and 2097 cm −1 were assigned to the terminal cyanide and the bridging cyanide ions, respectively.…”
Section: Ft-ir Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…The splitting of ν(Cl-O) band clearly indicated the presence of coordinated perchlorate. 21 In complex 2, the FT-IR spectrum ( Figure S2, in Supplementary Information) showed strong band at 3247 cm −1 which was assigned to secondary amine group. The vibrations from cyanide ligand may vary depending on the bonding mode, 22 24 the two absorption bands observed at 2117 and 2097 cm −1 were assigned to the terminal cyanide and the bridging cyanide ions, respectively.…”
Section: Ft-ir Spectroscopymentioning
confidence: 99%
“…Similar type of ESI mass spectral pattern was also observed in the hexaazamacrocyclic copper(II) complex reported previously. 21 Based on the physico-chemical and the spectral studies, the structure proposed for 1 is shown in Figure 1.…”
Section: Esi-ms Spectroscopymentioning
confidence: 99%
“…Transition-metal compounds have been of great interest and importance for researchers since they play a critical role in the development of coordination chemistry in structures such as one-dimensional chains, two-dimensional layers, three-dimensional frameworks and especially metal-organic frameworks (MOFs) (Paul et al, 2016;Pal et al, 2016;Kongchoo et al, 2016). They have great potential applications, for example, as luminescent probes, in catalysis (Gungor et al, 2014), as sensors (Zheng et al, 2016), in nonlinear optics (Karakas et al, 2006), as single-molecule magnets (SMMs) (Kahn, 1993;Caneschi et al, 2015;Blacque et al, 2016) and for exhibiting biological activities (Jamaludin et al, 2016), and also in solar-cell and photovoltaic technologies (Freitag et al, 2016;Magni et al, 2016).…”
Section: Introductionmentioning
confidence: 99%